GANGGUAN YANG TERJADI PADA SISTEM JOINTING PADA SALURAN KABEL TEGANGAN MENENGAH 20 KV - Nurmiati Pasra; Andi Makkulau; Muhamamd Hasil Adnan (Sekolah Tinggi Teknik - PLN, 2018)
In distributing electrical energy to customers, required a reliable power system. Disturbances in a system of electricity can not be avoided. Generally disruption of the underground channels, prone to disturbance occurs in cable connections (Jointing). Interference that occurs in SKTM in jointing that is existence of partial discharge. From the cable test results of a feeder Debur B 329 to B 162 this is a very bad cable condition. The location of the bad cable is at a distance of 59 to 91 m and 190 to 220 m, with a capacity of 0.272 μF and a frequency of 353.98 Hz. The cable testing to determine the existance on the cable channel and location of the occurance of interference so that it can be done immediately repair or replacement on the cable that has interference.